(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article analyzes the conditions of use and the main characteristics of greases. Dozens of brands of greases are used during the assembly and operation of the car. The performance properties of greases, unlike the performance properties of motor oils, should not only reduce friction and wear, but also have vibration resistance, colloidal stability, stickiness with contacting surfaces, mobility and pumpability. We have studied: the conditions of use and the main characteristics of greases that affect the operation of the units. And it was also considered ways to reduce the wear of car parts using greases with various additives. Too sticky grease is usually squeezed out with difficulty and can lead to overheating of the bearings. Taking into account the ability to form a strong film on the metal surface and a wide range of operating temperature, we conducted a number of experiments using molybdenum disulfide in laboratory conditions. The study shows that the use of molybdenum disulfide MoS2 additives to greases reduces the wear of parts, increases the life of friction units and reduces the likelihood of high-loaded parts being bullied and elasticity at low temperatures.